ASSOCIATION OF DELETION 13Q14 WITH CLINICOPATHOLOGIC FEATURES IN CHRONIC LYMPHOCYTIC LEUKEMIA - Ahmed, Ali; Hussain, Ch Altaf; Naeem, Mohammad Abdul; Malik, Hamid Saeed; Khan, Maria; Korejo, Saqib Hussain (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the frequency of Del 13q14 in Chronic lymphocytic leukaemia, to compare its association with clinicpathologic features and to define the contribution of this abnormality to the prognosis.Study Design: Cross-sectional study.Place and Duration of Study: Department of Haematology, Armed Forces Institute of Pathology, Armed Forces Bone Marrow Transplant Centre and Oncology department, Combined Military Hospital Rawalpindi, from Apr 2017 to Jul 2018.Methodology: A total of 56 newly diagnosed cases of CLL were included in the study. Patients were diagnosed on the basis of National Cancer Institute Working Group guidelines for diagnosis of CLL. After detailed history and thorough clinical examination; complete blood counts, biochemical profile, bone marrow examination, immunophenotyping on bone marrow or peripheral blood samples were done and Interphase FISH studies on blood or bone marrow specimens for detection of Del 13q14 were performed. Clinico-pathological features of CLL patients with Del 13q14 were compared with other cytogenetic abnormalities.Results: The frequency of Trisomy 12 was found to be 37.5%. Most of CLL patients with Del 13q14 were aymptomatic and were diagnosed on routine workup. The WBC count and Absolute lymphocyte count was slightly lower in patients with Del13 q14 lower when compared with the CLL patients without 13q14 Deletion. Most of the patients with this aberration presented in early stage (Binet stage A) and this association of Del 13q14 with Binet stage was statistically significant (p